2011
DOI: 10.1177/1534735410397044
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Therapy for Cancer-Related Fatigue in Patients With Breast Cancer Receiving Radiation Therapy: A Randomized Controlled Pilot Study

Abstract: Background Cancer-related fatigue (CRF) is the most frequently reported side effect of cancer and its treatment. In previous research, Polarity Therapy (PT), an energy therapy, was shown to reduce CRF in patients receiving radiation. This study reports on a small randomized clinical trial designed to collect preliminary data on the efficacy of PT compared with an active control (massage) and passive control (standard care) for CRF among cancer patients receiving radiation therapy. Methods Forty-five women un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
(43 reference statements)
0
37
0
Order By: Relevance
“…Previous research has shown long-term effect of different modalities of massage in cancer-related symptoms in breast cancer survivors (Billhult et al 2007;Imanishi et al 2009;Listing et al 2009Listing et al , 2010Sturgeon et al 2009;Krohn et al 2011;Mustian et al 2011). However, several of these studies did not obtain improvements in mood state in these patients (Billhult et al 2007;Krohn et al 2011).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous research has shown long-term effect of different modalities of massage in cancer-related symptoms in breast cancer survivors (Billhult et al 2007;Imanishi et al 2009;Listing et al 2009Listing et al , 2010Sturgeon et al 2009;Krohn et al 2011;Mustian et al 2011). However, several of these studies did not obtain improvements in mood state in these patients (Billhult et al 2007;Krohn et al 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Different modalities of massage tested in high-quality trials have shown to be effective during (Billhult et al 2007(Billhult et al , 2009Sturgeon et al 2009;Sharp et al 2010) and after (Imanishi et al 2009;Listing et al 2009Listing et al , 2010Krohn et al 2011) cancer treatment; however, some types of massage based on superficial manoeuvres have not shown to be effective (Billhult et al 2008). Furthermore, moderate effect sizes for improving quality of life of patients suffering cancerrelated fatigue had been found using polarity therapy (Mustian et al 2011). Nevertheless, psychophysiological mechanisms involved within massage applied over patients with cancer-related fatigue have not been clarified (Krohn et al 2011;Mustian et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…healing touch, 94 homeopathy,[263][264][265] hypnosis, 97 laser therapy, 111 manual lymphatic draining, 113 massage, 87 meditation, 26,72 movement,235,264 music therapy, 89 multimodal,199,210,230,236,237,267 multivitamin,238 polarity therapy,239,240 relaxation,69,77 shenqi fuzheng,202 shark cartilage,268 soy,149 supportive-expressive group therapy,269 tai chi 214,[270][271][272] Physical functioningMind-body cognitive therapy,234 music therapy, 33 multimodal, 199 myofascial release, 209 reflexology,139 stress management, 37 tai chi,270,272 yoga 45,79,84,273…”
mentioning
confidence: 99%
“…(Aghabati, Mohammadi, & Pour Esmaiel, 2010;Ahles et al, 1999; Currin & Meister, 2008;Fernández-Lao et al, 2012;FitzHenry et al, 2014; Karagozoglu & Kahve, 2013; Khiewkhern, Promthet, Sukprasert, Eunhpinitpong, & Bradshaw, 2013;Lutgendorf et al, 2010; Mehling et al, 2012;Mustian et al, 2011;Post-White et al, 2003;Roscoe, Matteson, Mustian, Padmanaban, & Morrow, 2005;Tsang, Carlson, & Olson, 2007; van den Berg, Visser, Schoolmeesters, Edelman, & van den Borne…”
mentioning
confidence: 99%